2011
DOI: 10.1111/j.1600-0501.2010.02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Location of posterior superior alveolar artery and evaluation of maxillary sinus anatomy with computerized tomography: a clinical study

Abstract: The results from this study suggested that CT scan is a valuable tool in evaluating presence of sinus pathology, septa, and arteries before maxillary sinus surgery. Although variations exist in every patient, the findings from this study suggest limiting the superior border of the lateral window up to 18 mm from the ridge to avoid any potential vascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
125
9
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(170 citation statements)
references
References 14 publications
25
125
9
11
Order By: Relevance
“…The artery was observed in 89.3% of the sinuses and was mostly intraosseous (71.1%). The success rate for identifying the artery was higher than that reported by Güncü et al 13 (64.5%), Elian et al 14 (52.9%), Mardinger et al 15 (55%), and Kim et al 16 (52%). This may be related to the methods the other groups used to detect and describe the artery.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…The artery was observed in 89.3% of the sinuses and was mostly intraosseous (71.1%). The success rate for identifying the artery was higher than that reported by Güncü et al 13 (64.5%), Elian et al 14 (52.9%), Mardinger et al 15 (55%), and Kim et al 16 (52%). This may be related to the methods the other groups used to detect and describe the artery.…”
Section: Discussioncontrasting
confidence: 52%
“…1,2 We observed a shorter distance than in these anatomic studies. The differences may be due to the small number of cases evaluated with CT in previous studies as reported by Güncü et al 13 (18 mm), Elian et al 14 (16.4 mm), Mardinger et al 15 (16.9 mm), and Kim et al 16 (18.9 mm). Our current results are close to those of these studies.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations